β-CATENIN stabilizes HIF2 through lncRNA and inhibits intravenous immunoglobulin immunotherapy - Nakagawa, Chad; Kadlera Nagaraj, Manjunatha; Hernandez, Juan Carlos; Uthay Kumar, Dinesh Babu; Shukla, Vivek; Machida, Risa; Schüttrumpf, Jörg; Sher, Linda; Farci, Patrizia; Mishra, Lopa; Tahara, Stanley M.; Ou, Jing-Hsiung James; et al. (Frontiers in Immunology, 2023)
Introduction Tumor-initiating cells (TICs) are rare, stem-like, and highly malignant. Although intravenous hepatitis B and C immunoglobulins have been used for HBV and HCV neutralization in patients, their tumor-inhibitory effects have not yet been examined. Hepatitis B immunoglobulin (HBIG) therapy is employed to reduce hepatocellular carcinoma (HCC) recurrence in patients after living donor liver transplantations (LDLT). Hypothesis We hypothesized that patient-derived intravenous immunoglobulin (IVIG) binding to HCC associated TICs will reduce self-renewal and cell viability driven by β-CATENIN-downstream pathways. β-CATENIN activity protected TICs from IVIG effects. Methods The effects of HBIG and HCIG binding to TICs were evaluated for cell viability and self-renewal. Results Inhibition of β-CATENIN pathway(s) augmented TIC susceptibility to HBIG- and HCIG-immunotherapy. HBV X protein (HBx) upregulates both β-CATENIN and NANOG expression. The co-expression of constitutively active β-CATENIN with NANOG promotes self-renewal ability and tumor-initiating ability of hepatoblasts. HBIG bound to HBV+ cells led to growth inhibition in a TIC subset that expressed hepatitis B surface antigen. The HBx protein transformed cells through β-CATENIN-inducible lncRNAs EGLN3-AS1 and lnc-β-CatM. Co-expression of constitutively active β-CATENIN with NANOG promoted self-renewal ability of TICs through EGLN3 induction. β-CATENIN-induced lncRNAs stabilized HIF2 to maintain self-renewal of TICs. Targeting of EGLN3-AS1 resulted in destabilization of EZH2-dependent β-CATENIN activity and synergized cell-killing of TICs by HBIG or HCIG immunotherapy. Discussion Taken together, WNT and stemness pathways induced HIF2 of TICs via cooperating lncRNAs resulting in resistance to cancer immunotherapy. Therefore, therapeutic use of IVIG may suppress tumor recurrence through inhibition of TICs.